2018
DOI: 10.7759/cureus.2702
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hypoxic Reversible Leukoencephalopathy Syndrome

Abstract: We report a case of postanoxic leukoencephalopathy in a patient who started to have cognitive and behavioral changes weeks after the anoxic insult along with white matter lesions on neuroimaging and demyelination on brain biopsy. His disease course followed a steady decline initially both clinically and radiologically and assumed a steady plateau. Months after his decline, the patient was seen to be completely functional with substantially improved mental status examination and resolution of white matter chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the study by Sputcher et al, the evidence of demyelination with increased myelin-based protein in the cerebrospinal fluid in a case of DPHL associated with prolonged coma following opioid poisoning supported the role of myelin-based protein in this disorder [4]. There are also reports of arylsulfatase deficiency in patients with DPHL [7]. In another study, an autopsy of a patient with DPHL revealed evidence of subcortical myelin sheath loss without U-fiber involvement with prominent macrophage/microglial inflammation and extensive axonal damage [8].…”
Section: Discussionmentioning
confidence: 93%
“…In the study by Sputcher et al, the evidence of demyelination with increased myelin-based protein in the cerebrospinal fluid in a case of DPHL associated with prolonged coma following opioid poisoning supported the role of myelin-based protein in this disorder [4]. There are also reports of arylsulfatase deficiency in patients with DPHL [7]. In another study, an autopsy of a patient with DPHL revealed evidence of subcortical myelin sheath loss without U-fiber involvement with prominent macrophage/microglial inflammation and extensive axonal damage [8].…”
Section: Discussionmentioning
confidence: 93%
“…Toxic exposure may cause myelinopathy and subsequent demyelination by impairing ATP-dependent enzymes responsible for myelin turnover in the deep white matter [1,15]. Deep white matter injury in DTHL may be a manifestation of the vulnerability of the deep white matter to hypoxia-ischemia [2]. Unlike the corpus callosum and U-fibers, the deep white matter is supplied by widely spaced arterioles with few anastomoses [1,18].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed post-hypoxic leukoencephalopathy (DPHL), also known as Grinker myelinopathy, delayed anoxic encephalopathy, or post-interval syndrome, is a rare complication of hypoxic-ischemic brain injury [1]. DPHL is characterized by a biphasic clinical course, with initial complete or near-complete recovery from cerebral anoxia, followed by clinical stability over a period of weeks (lucid interval), and subsequent neurological deterioration due to diffuse white matter disease [2]. It has nearly been a century since Grinker recognized the link between delayed leukoencephalopathy and anoxic brain injury [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation